Toward a dynamic analysis of bipedal robots inspired by human leg muscles - Fernini, B.; Temmar, M.; M. M., Noor (Faculty Mechanical Engineering, UMP, 2018)
A walking bipedal robot by adding passive springs like mono and biarticular muscles which correspond to rectus femoris (RF), biceps femoris (BF), gastrocnemius (GAS) and tibialis anterior (TA) in human legs has been modeled in this paper. The stability of human-like leg walking can be achieved by adding these passive springs in the leg mechanism of bipedal robot. On the other hand, using these springs may inflict a fatigue during walking due to the additional work that can provide to the joints. The main objective of this paper is to analyze the total work of the robot during walking by proposing four cases of the preload of the springs at the equilibrium position. It’s found from this study that the case that has the most energy saving and ensure the comfortable walking to the robot is when the two muscles (GAS) and (TA) are not preloaded to support the total weight at the equilibrium position.